2011
DOI: 10.1148/radiol.10100354
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Benefit of Computer-aided Detection when Used as a Second and Concurrent Reader of CT Colonographic Data: Multiobserver Study

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.10100354/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 24 publications
0
63
1
1
Order By: Relevance
“…q RSNA, 2013 TECHNICAL DEVELOPMENTS: Method for Tracking Eye Gaze during Interpretation of 3D CT Colonography Phillips et al colonography data, which had been collected during two previous studies (8,9), for eye tracking and to record data from six readers who were recruited from attendees at the 12th U.K. Virtual Colonoscopy Workshop, which was held November 16 and 17, 2009, in London, England.…”
Section: Discussionmentioning
confidence: 99%
“…q RSNA, 2013 TECHNICAL DEVELOPMENTS: Method for Tracking Eye Gaze during Interpretation of 3D CT Colonography Phillips et al colonography data, which had been collected during two previous studies (8,9), for eye tracking and to record data from six readers who were recruited from attendees at the 12th U.K. Virtual Colonoscopy Workshop, which was held November 16 and 17, 2009, in London, England.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit they observed was mainly due to increased detection of medium and small-sized polyps. However, the magnitude of benefit was not as pronounced as for second-read CAD, when the two paradigms were compared directly on the same datasets and readers [13]. The reasons underpinning the lower diagnostic performance of concurrent reading are not yet well understood.…”
Section: How To Use Cadmentioning
confidence: 92%
“…These authors also found that CAD second-read increases detection of intermediate size polyps. Recently, Halligan et al [13] demonstrated that second-read CAD also benefits the experienced CTC reader, finding that mean per-polyp sensitivity for polyps 6 mm or larger increased on average by 9%. As expected, additional interpretation of CAD candidates extends overall CTC reading time by a few minutes [12,14].…”
Section: How To Use Cadmentioning
confidence: 99%
“…Institutional review board and research ethics committee approval was granted to use anonymous CTC data collated in previous studies. 22,23 Participants and cases 13 radiologists (readers) were recruited from a UK training hospital over 2 days in July 2012. All provided written, informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Five videos depicted a single colorectal polyp (true positive, 5-8 mm maximal transverse dimension), verified by three radiologists with .200 cases' experience. 23 To counteract recall, cases were excluded if they contained polyps within 5 s navigation of the caecal pole, rectal ampulla or insufflation catheter, or contained other distinctive characteristics, assessed by a radiologist with 6 years' experience (EH). Polyps were on screen for between 2.4 and 11.1 s. The remaining five videos (true negative) were selected from different sections of the colon, containing no polyps, in the same patient group.…”
Section: Methodsmentioning
confidence: 99%